(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Sedation is frequently undertaken for radiological imaging procedures in paediatric patients. Movement during procedure degrades all images of a particular sequence. A deeper level of sedation is needed. The sedation of children is different from the sedation of adult. The safe sedation of children for imaging procedure requires a systematic approach that includes the followings. Careful presedation health evaluation of the child with ASA classification. Appropriate fasting guidelines for sedation procedure. Detailed airway examination for any airway abnormalities that might increase the potential for airway obstruction. Adequate training and skills of sedating personnel in paediatric airway management. Age and size appropriate equipment for airway management and venous access. Adequate medications to combat adverse events. Monitoring of vital parameters during and after the procedure. A properly equipped and staffed recovery area. Recovery to presedation level of consciousness of patient before discharge from medical supervision and appropriate discharge instructions. The whole procedure should be well documented. Children who have contraindications to sedation should be selected for general Anaesthesia. This review article has been made to discuss the need for sedation of children during radiological imaging, currently practiced different regimens of sedation, safe guidelines for sedation and also covers the debate between need for GA versus sedation. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19805 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 70-76